Membrane electrode assembly hybridized anaerobic digester for co-generation of methane enriched biogas and electricity. (15th May 2022) - Bora, Deep; Dutta, Arup; Mahanta, Pinakeswar; Goswami, Pranab; Stom, Devard; Barbora, Lepakshi
Graphical abstract: Highlights: Bio electrochemical processing of cattle dung for enriched biogas and electricity. An increment of 17.4 % methane on hybridization of anaerobic digester with MEA. The hybridized AD-MEA setup could produce as high as 496 ± 7 mV OCV. The AD-MEA facilitates syntrophic interactions among electrogens and methanogens. CV affirmed the presence of electrogenic bacteria in the cattle dung slurry. Abstract: The endeavor for utilization of various kinds of organic wastes into a valuable energy source through the process of anaerobic digestion is gaining ground amongst the researchers worldwide. In this context, a single chamber, above the ground, portable anaerobic digester (AD) was developed which was hybridized with a membrane electrode assembly (MEA) to facilitate the generation of enriched biogas and electricity as a byproduct. The analysis showed enrichment of CH4 in the biogas, while the AD was hybridized with the MEA. The highest concentration of CH4 in control was 56.3 ± 1.5% whereas in AD-MEA, the concentration of CH4 increased to 73.7 ± 3.9%. Thus, the incorporation of conductive surface in the anaerobic chamber of the AD-MEA system could promote the enrichment of methane. The presence of the non-biological conductive surface in the anaerobic chamber stimulated syntrophic interactions among exoelectrogens and hydrogenotrophic methanogens for conversion of CO2 directly to CH4 . Moreover, the hybridized AD-MEA system could produce a maximum of 496 ± 7 mV OCV, with a maximum average power density of 2.87 mW/m 2 and 70 mA/m 2 current density.